Relationship Between Age and Blood Pressure in Patients Postoperative Sectio Caesarea - Heliyana HR, Okto; Susanto, Amin; Netra Wirakhmi, Ikit (Java Nursing Journal, 2024)
Background: Cesarean section (C-section) is a surgical procedure for childbirth, involving an incision in the uterine wall through the abdomen, typically indicated for various medical reasons. Spinal anesthesia is commonly employed during C-sections, although it is associated with side effects such as fluctuations in blood pressure. The majority of C-section patients under spinal anesthesia are between 20 and 35 years of age, considered the optimal reproductive years for pregnancy and childbirth. Purpose: This study aims to evaluate the correlation between age and blood pressure in postoperative C-section patients under spinal anesthesia. Methods: A cross-sectional, observational-analytical study design was used, involving 81 purposively sampled respondents. Data were analyzed using Spearman's rank correlation to assess the relationship between age and blood pressure postoperatively. Findings: The majority of respondents (67.9%) were aged between 20 and 35 years. Postoperative blood pressure in the recovery room was predominantly within the normal range, with 71.6% of patients displaying normal blood pressure levels. A statistically significant correlation was found between age and blood pressure, with a p-value ≤ 0.05. Conclusion: Age is significantly associated with postoperative blood pressure in patients undergoing C-sections under spinal anesthesia. This finding highlights the importance of monitoring blood pressure in this population to ensure optimal recovery outcomes.